2021
DOI: 10.1007/s00371-021-02242-y
|View full text |Cite
|
Sign up to set email alerts
|

Can a humanoid social robot stimulate the interactivity of cognitively impaired elderly? A thorough study based on computer vision methods

Abstract: Social Assistive Robotics is increasingly being used in care settings to provide psychosocial support and interventions for the elderly with cognitive impairments. Most of these social robots have provided timely stimuli to the elderly at home and in care centres, including keeping them active and boosting their mood. However, previous investigations have registered shortcomings in these robots, particularly in their ability to satisfy an essential human need: the need for companionship. Reports show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 93 publications
(84 reference statements)
0
31
0
Order By: Relevance
“…The overall findings were mixed; some studies suggested therapeutic effects of the robots, whereas others were neutral or inconclusive. The most commonly reported benefits of the social robots were improved mood and emotional states [ 33 , 41 , 42 , 44 , 49 , 52 , 55 , 72 , 74 , 76 , 78 , 80 , 81 , 84 , 85 , 87 , 92 - 94 ] and an increase in social interaction between the residents and other human interactors [ 31 , 36 , 41 , 42 , 52 , 55 , 58 , 59 , 63 , 69 , 72 , 75 , 81 , 82 , 95 - 98 ], including caregivers [ 69 ] and preschoolers [ 59 ]. Other commonly reported benefits of the robots were reduced loneliness [ 36 , 92 , 99 ], evoked positive memories of pets [ 59 , 65 , 85 , 96 , 100 ], improved quality of life [ 53 , 79 ] and well-being [ 65 ], reduced pain and pain medication use [ 85 , 86 ], cognitive stimulation [ 31 , 59 , 78 ], and improved behavior [ 49 , 55 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall findings were mixed; some studies suggested therapeutic effects of the robots, whereas others were neutral or inconclusive. The most commonly reported benefits of the social robots were improved mood and emotional states [ 33 , 41 , 42 , 44 , 49 , 52 , 55 , 72 , 74 , 76 , 78 , 80 , 81 , 84 , 85 , 87 , 92 - 94 ] and an increase in social interaction between the residents and other human interactors [ 31 , 36 , 41 , 42 , 52 , 55 , 58 , 59 , 63 , 69 , 72 , 75 , 81 , 82 , 95 - 98 ], including caregivers [ 69 ] and preschoolers [ 59 ]. Other commonly reported benefits of the robots were reduced loneliness [ 36 , 92 , 99 ], evoked positive memories of pets [ 59 , 65 , 85 , 96 , 100 ], improved quality of life [ 53 , 79 ] and well-being [ 65 ], reduced pain and pain medication use [ 85 , 86 ], cognitive stimulation [ 31 , 59 , 78 ], and improved behavior [ 49 , 55 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study illuminated safety concerns regarding relatives responding to emergencies via a telepresence robot instead of caregivers [ 64 ]. Barriers to use included technical difficulties [ 38 , 45 , 51 , 54 , 57 , 64 , 77 , 84 , 95 ], difficulty hearing [ 64 , 85 , 88 , 102 ] and seeing [ 48 ] the robots, and physical limitations [ 48 , 51 , 85 , 96 , 100 ]. However, other studies found the robots easy to use despite cognitive impairments and technological illiteracy [ 45 , 57 , 67 , 68 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there is no publicly available labeled dataset for learning ERI, not to mention that in a multiparty scenario. In our work, we created a labeled one by utilizing a dataset called BHEH dataset 53,54 . The BHEH dataset is video recordings of real ERI.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…In our work, we created a labeled one by utilizing a dataset called BHEH dataset. 53,54 The BHEH dataset is video recordings of real ERI. There was no constraint imposed on the participants.…”
Section: Bheh Datasetmentioning
confidence: 99%